Government's role in attracting MNCs: a case study of Malaysia / Noorain Mohd Ariff (Faculty of Business and Management, 2007)
The purpose of this study is to identify the factors that make Malaysian market is attractive to MNCs and to determine the relationship between Malaysia's financial factors, economic factors and social factors with the inward investment, as the Government is seeking a way to promote a balanced industrial development. This research is also hoped to act as a knowledge contribution to this subject area by identifying the benefits of the MNCs and the factors that will attract MNCs to a host country. It is also to find out whether both MNCs and the host country will get maximum benefits from the international trade activities. The secondary data were used and the collected data were processed using the SPSS Software and Microsoft Excel. The results suggest that level of development and literacy had a positive relationship with the FDI inflows, while the current account position, economic growth and interest rates had a negative relationship with the inflows of FDI. However, only the level of development and the economic growth variables were statistically significant. The current account, interest rates and educational level are not significantly determining the FDI inflows. This study might provide an insight for the Government as to ascertain and identify the roles and actions to be taken in order to improve the country's economic and development as both shows a significant correlation and relationship with the inflows of FDI to Malaysia.